Optimizing Starch Extraction from Porang Glucomannan Extraction Residue using Ultrasonic-Assisted Extraction: A Comparative Approach - Arshy, Nurul Fadillah; Pranoto, Yudi; Manikharda, Manikharda (Trends in Sciences, 2025)
This study optimized starch extraction from porang glucomannan extraction residue (PR) using Response Surface Methodology (RSM) with a Box-Behnken design. Ultrasonic-Assisted Extraction (UAE) was employed, focusing on sonication power, extraction time, and solid-to-solvent ratio. A second-order polynomial model with high accuracy (R² = 0.9972) identified optimal conditions as 119.97 W sonication power, a 1:39.88 g/mL solid-to-solvent ratio, and 18.89 min extraction time. The experimental yield of 77.54 % surpassed the predicted value, confirming UAE’s efficiency for industrial-scale extraction. Optimized porang starch (OPS) showed the highest starch (67.80 %) and amylose (24.73 %) content, while starch from residue (OPRS) had lower starch (55.69 %) and amylose (7.51 %) but higher amylopectin (48.18 %). Color analysis revealed lighter, whiter starches, indicating effective pigment removal. FTIR confirmed the structural integrity and purity of both OPS and OPRS, while XRD showed comparable crystallinity, with a slight increase in OPRS. Microscopic analysis revealed uniform, smoother granules in OPS. DSC analysis indicated higher thermal stability and gelatinization temperatures in OPS compared to porang starch (PS) and porang flour (PF). These findings highlight UAE as an effective method for extracting high-quality starch from porang residue, with potential applications in industries, supporting sustainable practices and efficient resource utilization. HIGHLIGHTS Optimized starch extraction from porang residue achieved 54 % recovery using Ultrasonic-Assisted Extraction (UAE). Optimal UAE conditions: 119.97 W power, 18.89 min, and 1:39.88 g/mL solid-to-solvent ratio. Optimized porang starch showed higher amylose content (24.73 %) and improved thermal stability. FTIR, XRD, and DSC analyses confirmed starch purity and enhanced structural properties. UAE demonstrated sustainability and potential for high-quality industrial starch extraction. GRAPHICAL ABSTRACT